Suits. Season eight [videorecording (DVD)] - Macht, Gabriel, 1972-; Hoffman, Rick, 1970-; Rafferty, Sarah; Heigl, Katherine (Universal Pictures Home Entertainment, 2019)
With Mike's departure, Harvey and Louis are left in joint control of the firm while another powerhouse lawyer sees her chance to force her way into the high-profile team.